Improving Medical Education: Simulating Changes in Patient Anatomy Using Dynamic Haptic Feedback. (September 2016) - Yovanoff, Mary; Pepley, David; Mirkin, Katelin; Moore, Jason; Han, David; Miller, Scarlett
Virtual simulation is an emerging field in medical education. Research suggests that simulation reduces complication rates and improves learning gains for medical residents. One benefit of simulators is their allowance for more realistic and dynamic patient anatomies. While potentially useful throughout medical education, few studies have explored the impact of dynamic haptic simulators on medical training. In light of this research void, this study was developed to examine how a Dynamic-Haptic Robotic Trainer (DHRT) impacts medical student self-efficacy and skill gains compared to traditional simulators developed to train students in Internal Jugular Central Venous Catheter (IJ CVC) placement. The study was conducted with 18 third year medical students with no prior CVC insertion experience who underwent a pre-test, simulator training (manikin, robotic, or mixed) and post-test. The results revealed the DHRT as a useful method for training CVC skills and supports further research on dynamic haptic trainers in medical education.